Analisis dan Perancangan Sistem Pengendalian Intern Penjualan pad Industri Batik (Studi Kasus: PT Komar Caruban Nagari Bandung) - Gina Siti Nur Afiah; Vina Citra Mulyandani; Yanti Rufaedah; Riauli Susilawaty Hutapea; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to analyze and design a sales internal control system at PT Batik Komar Caruban Negeri Bandung. The research was conducted using a qualitative descriptive method with a case study type. This study uses primary data and secondary data obtained from PT Batik Komar Caruban Negeri Bandung. The data used in this study were collected in detail through a triangulation procedure (a combination of interviews, observation and documentation). The data analysis tool used is the control matrix based on the COSO (Committee of Sponsoring Organizations) framework. The research results show that the sales internal control system at PT Komar Caruban Nagari has been running but is not optimal because there are still several elements that have not been implemented. Therefore, from the results of an analysis of the sales accounting system and internal sales control system that has been running, the author designed a sales internal control system and the design was approved to be implemented in stages in the company.